Exploration of Islamic Values in Islamic Banking (Study of Islamic Bank Customer Perspective in Makassar) - Misbach, Irwan (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2019)
This study explores Islamic values in the operations of Islamic banks based on the perspective of customers in Makassar City. Based on factor analysis, 4 factors are found. Factor 1 contains